The Role of Mentawai Night in Cultural Preservation and Increasing Social Participation of the Mentawai Community - Asnur, Lise; Fransiska, Serly Dwi; Mardhiyah, Mardhiyah; Putra, Sandra Yusda; Vanni, Vino Gion; Nofrializa, Nofrializa (Universitas Pahlawan Tuanku Tambusai, 2025)
Mentawai Night is a regular cultural agenda serving a dual and crucial role in preserving local cultural heritage and increasing social participation among the Mentawai community. By featuring traditional arts and rituals, such as the Sikerei dance or gong music, and actively involving all community segments, the event not only provides a platform for authentic cultural expression but also significantly strengthens social cohesion and bonds. Nevertheless, organizers face significant challenges: a massive surge in visitors is typically observed only on the opening night, followed by a sharp decline in attendance during the subsequent week of the event. Therefore, innovative sustainability strategies—including program diversification or interactive workshops—are essential to maintain the event's appeal and relevance throughout its entire duration. By addressing these challenges, Mentawai Night holds substantial potential to evolve into an inclusive, self-sufficient, and sustainable model for community-based cultural activities for other island territories.